Academics’ research productivity dynamics: psychological needs, research orientation, and desire for recognition - Albaram, Badr Mohammed; Lim, Yet Mee; Keoy, Kay Hooi; Siek, Hwee Ling (International Journal of Evaluation and Research in Education (IJERE), 2025)
Malaysian higher education institutions aim to improve their reputation and visibility by focusing on research publications. Consequently, they face complexity in motivating research productivity compared to the high demand for academic research output and diversity of academics. This paper aims to fill the knowledge gap in investigating the dynamics of research productivity through the interplay of psychological needs satisfaction (PNS) to share knowledge, research orientation, and desire for recognition as intrinsic motivators. This quantitative research surveyed academics (N=310) in public and private Malaysian universities and data was analyzed using partial least squares structural equation modeling (PLS-SEM). The findings revealed that both research orientation and desire for recognition play a critical role in motivating academics’ research productivity. Additionally, the study demonstrates that when academics perceive their psychological needs as satisfied, they engage in knowledge-sharing behavior (KSB), which positively affects research productivity, though not as significantly as previously assumed. The study contributes to the literature as pioneering research investigated the role of research orientation, and desire for recognition in motivating academics’ research productivity. It widens the decision makers awareness in higher education institutions to understand the intrinsic motivations of research productivity that motivate them to develop research productivity policies.